2021
DOI: 10.3389/fmed.2021.690594
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Genes and Pathways in Persistent Hyperplastic Primary Vitreous of the Eye Using Bioinformatic Analysis

Abstract: Graphical AbstractSchematic diagram for evaluating and identifying the key genes, molecular pathways, predicted drug targets of PHPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…PFV occurs when regression of the embryological primary vitreous and hyaloid vasculature fails to occur, and dysregulation of apoptosis has been theorized to be a potential cause. 11 However, the exact pathogenic mechanism remains unclear. In zebrafish, the Bcl6 ortholog Bcl6a has been shown to suppress p53-dependent apoptosis during embryogenesis to prevent formation of colobomata.…”
Section: Discussionmentioning
confidence: 99%
“…PFV occurs when regression of the embryological primary vitreous and hyaloid vasculature fails to occur, and dysregulation of apoptosis has been theorized to be a potential cause. 11 However, the exact pathogenic mechanism remains unclear. In zebrafish, the Bcl6 ortholog Bcl6a has been shown to suppress p53-dependent apoptosis during embryogenesis to prevent formation of colobomata.…”
Section: Discussionmentioning
confidence: 99%
“…The isolated fibrovascular stalk in our case suggests an uncomplete regression course. We referred to the pathogenesis of PHPV in the literature, it has been reported that a number of genes and pathways primarily associated with eye morphogenesis, the apoptotic process, autophagy, and the angiogenic process were involved in the regression of hyaloid vasculature [ 23 ]. Besides, the macrophages may also play a central role in the blocking of blood flow, induction of apoptosis, and clearance of atrophic vessels during regression of the hyaloid vascular system [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment results were obtained by analyzing significant genes in each of the three data sets using KEGG Mapper (Supplemental sheets 1, 2, and 3). 33 ShinyGO was used to create a pathway visualization of the common 10 significant genes.…”
Section: Go and Pathway Enrichment Analysismentioning
confidence: 99%